The Effect of Gadget Usage Duration on Students' Reading Interest at Madrasah Ibtidaiah Muhammadiyah 16 Karangasem - Ningtias, Rahayu Kusuma; Zativalen, Oriza; Khasanah, Linaria Arofatul Ilmi Uswatun (Raja Zulkarnain Education Foundation, 2025)
This study aims to determine the effect of gadget usage duration on students’ reading interest at MI Muhammadiyah 16 Karangasem. The increasing use of gadgets among elementary school students may divert their attention from reading activities. A significant number of students tend to spend more time on gadgets than reading books, which potentially leads to a low level of reading interest. This research employed a quantitative approach with a survey design. The sample consisted of 87 students from grades 4 and 5, who were divided into three groups based on their gadget usage duration: high, medium, and low. The instruments used were questionnaires that measured gadget usage duration and the level of reading interest based on four indicators: enjoyment in reading, interest, attention, and engagement in reading. The data analysis techniques included validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis testing using One-Way Anova. The results showed a significant difference in reading interest based on the duration of gadget usage. The calculated F value was 7.373 with a significance level of 0.001, indicating that gadget usage duration significantly affects students’ reading interest. The average reading interest score for students with low gadget usage duration was 73.75, for medium duration was 77.17, and for high duration was 71.21. Based on these results, it can be concluded that the higher the duration of gadget usage, the lower the students’ reading interest tends to be.